Hay Yield, Chemical Composition, and In Vitro Digestibility of Five Varieties of Common Vetch - Xiao Cheng; Sunze Wang; Kefan Zhang; Ting Jiang; Yang Ye; Yuan Lu; Yajie Yu; Huiqing Wei; Zijun Zhang; Yafeng Huang (Agriculture, 2024)
Diversifying feed with annual legumes could help to reduce reliance on imported sources of alfalfa hay, ensuring a consistent supply of forage throughout year, and potentially decreasing the cost of raising ruminants. This study evaluated the varietal variability in hay yield, chemical composition, carbohydrate and protein fractions, and in vitro digestibility of five common vetch varieties used in this experiment during the full-flowering period in Jianghuai region during the 2022 crop season. Results showed that improved varieties (Lanjian No. 1 and Lanjian No. 2, 6.30 and 6.11 t DM/ha) had significantly higher hay yields than the local variety (333A, Longjian No. 1), with Lanjian No. 3 showing intermediate yields. Variety Lanjian No. 1 had the highest non-protein nitrogen concentration and in vitro digestibility, while Lanjian No. 2 had the highest starch concentration, fraction of intermediately degradable pectin and starch, and fraction of neutral detergent-soluble protein and acid detergent-soluble protein. Pearson correlation showed that hay yield was not significantly correlated with quality parameters. Principal component analysis showed that Lanjian No. 1 and Lanjian No. 2 received higher nutritive value. In summary, Lanjian No. 1 and Lanjian No. 2 had better potential use as high-protein feedstuffs for dairy cattle and sheep in the Jianghuai region based on yield, protein fractions, and in vitro digestibility.